Consciousness ain’t all that - Levy, N (Springer, 2024)
Most philosophers think that phenomenal consciousness underlies, or at any rate makes a large contribution, to moral considerability. This paper argues that many such accounts invoke question-begging arguments. Moreover, they’re unable to explain apparent differences in moral status across and within different species. In the light of these problems, I argue that we ought to take very seriously a view according to which moral considerability is grounded in functional properties. Phenomenal consciousness may be sufficient for having a moral value, but it may not be necessary, and it may contribute relatively little to our overall considerability.